"Canindé é quando dé" : trabalho e recompensa - Lima, Francisco John Lennon Alves Paixão (2016)
This dissertation focuses on the analysis and interpretation of the religious, sacred and profane space of the town of Canindé, Ceará, through of influence and meanings of São Francisco das Chagas party in the commerce and daily life of its townspeople. The research was made through questionnaires with traders and not traders residents and interviews with institutions representatives such as the Basilica de São Francisco das Chagas and the local prefecture. The applications of the questionnaires happened especially during the period of the festivities of the patron in 2014 (September and October) and in March 2015. It was held also researches in books, academic papers, newspapers and specific sites, as IBGE and IPECE. The cult of the saint promotes a periodic movement of pilgrims to Canindé, with greater expressiveness during the month dedicated to his birthday, and it is characterized while a cosmogonic movement (ELIADE, 1992), giving that space materialized meanings, especially in landscape and rituals in favor of the patron. The patron status and the perpetuation of pilgrimages, present in evident characterization in landscape of the city, because it is a religious space, ensures the continuity of the festival and of the city itself in time and space, as well as credit of city of religious function and hierópolis. The theoretical framework was based in classics of Cultural Geography as Carl O. Sauer: "The morphology of landscape"; in the work of Yi-Fu Tuan called "Space and Place: The Perspective of Experience"; in the book by Maria C. França entitled "Pequenos Centros Paulistas de Função Religiosa" and other areas as sociology with Mircea Eliade. The theoretical framework was also based on texts and books of the Cultural Geography collection of the EDUERJ publisher as well as in Brazilian productions. The results point to the existence of a sacred-profane interdependence experienced by the people of that city, who sees the patron's party as a means of living, income generation and as spiritual identity: the party is revealed as devotion to the saint, heating local economy and identity for families as "old residents and devouts in the city". Based on those authors, for its population, Canindé is a place, a safe and personal home; the center of the world to approximation of the saint; a Hierópolis (based on ROSENDAHL, 1996; COSTA, 2009) and a city of religious function. Despite the religious and economic importance of the party, it still brings a small result to the city: there is need for more investment in infrastructure, especially that dedicated to receive and the permanency of pilgrim in the city (hotel, food, transportation), especially to the poor; and also infrastructure investment for its population, mainly in leisure, education and increase enrollment of unlinked jobs religious. The infrastructure dedicated to the commercialization of products that express the religiosity in the patron, like medals, rosaries, images, prayer books, among others, as well as the infrastructure to pilgrims, shows remarkable growth, while still a small amount of recourses is reverted to the city to produce its well-being and quality of life.